2022
DOI: 10.7150/ijms.71820
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus is Associated with Gastric Cancer Precursor: Atrophic Gastritis

Abstract: Background: About 10% of gastric cancer (GC) has been described to be Epstein-Barr virus (EBV) positive. Previous researches have described the association between EBV and GC. However, the association of EBV with atrophic gastritis (AG) is underrecognized. Our study aimed to investigate the relationship between EBV and AG and assess the influence of EBV on gastric function. Methods: A total of 468 pathologically-confirmed chronic gastritis patients underwent circulating EBV DNA test, include 271 non-atrophic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…It is very difficult to collect EBVaGC cases without H. pylori infection, because most patients with gastric cancer are infected with H. pylori [ 33 , 34 ]. However, a clinical study was conducted to investigate the relationship between EBV infection, H. pylori infection, and atrophic gastritis in 468 patients with chronic gastritis[ 35 ]. This study confirmed that patients who were EBV-positive had a lower pepsinogen I/pepsinogen II ratio than patients who were EBV-negative.…”
Section: Inflammation and Carcinogenesismentioning
confidence: 99%
“…It is very difficult to collect EBVaGC cases without H. pylori infection, because most patients with gastric cancer are infected with H. pylori [ 33 , 34 ]. However, a clinical study was conducted to investigate the relationship between EBV infection, H. pylori infection, and atrophic gastritis in 468 patients with chronic gastritis[ 35 ]. This study confirmed that patients who were EBV-positive had a lower pepsinogen I/pepsinogen II ratio than patients who were EBV-negative.…”
Section: Inflammation and Carcinogenesismentioning
confidence: 99%
“…Moreover, Zhao et al have repeatedly identified the presence of EBV and H. pylori. in the mucosa of patients with moderate chronic atrophic gastritis [ 122 ].…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…Epstein‐Barr virus (EBV) is an infectious agent‐associated malignancy discovered in Burkitt lymphoma cells 1 and is causally associated with several human tumours, including Hodgkin lymphoma (HL), non‐Hodgkin lymphoma (NHL), nasopharyngeal carcinoma (NC), gastric carcinoma (GC) and lymphoepithelial carcinoma of several organs such as salivary glands, lung and liver 2–6 …”
Section: Introductionmentioning
confidence: 99%